Evaluation of Combined Ultrasonography and Cone Beam Computed Tomography for Clinical Imaging: A Negative Results Study - Flanagan Dennis; Tarakonova Anna; Pandey Anshika; Kumavor Patrick; Lo Carmen; Mundiwala Mohammad (Journal of Biotechnology and Biomedical Science, 2026)
The combination of ultrasonography (US) and cone beam computed tomography (CBCT) has been proposed as a multimodal imaging strategy capable of uniting realtime softtissue assessment with highresolution threedimensional visualization of osseous structures. This study critically evaluated whether such integration provides measurable diagnostic or workflow advantages in mandibular imaging. Despite strong theoretical justification, the combined use of US and CBCT failed to demonstrate clinically meaningful improvements in diagnostic accuracy, confidence, or efficiency when compared with CBCT alone. Fundamental physical mismatches, hardware incompatibilities, geometric constraints, and operatordependent variability limited the anticipated synergistic benefits. These negative findings underscore the importance of reporting unsuccessful integration attempts to guide future research and prevent premature clinical adoption of technically incompatible imaging paradigms.
Keywords: Cone beam computed tomography (CBCT)